A Therapeutic Potential of Animal β-hairpin Antimicrobial Peptides - V. Panteleev, Pavel; V. Balandin, Sergey; T. Ivanov, Vadim; V. Ovchinnikova, Tatiana (Current Medicinal Chemistry, 2017)
Endogenous antimicrobial peptides (AMPs) are evolutionary ancient molecular factors of innate immunity that play the key role in host defense. Because of the low resistance rate, AMPs have caught extensive attention as possible alternatives to conventional antibiotics. Over the last years, it has become evident that biological functions of AMPs are beyond direct killing of microbial cells. This review focuses on a relatively small family of animal host defense peptides with the β-hairpin structure stabilized by disulfide bridges. Their small size, rigid structure, stability to proteases, and plethora of biological functions, including antibacterial, antifungal, antiviral, anticancer, endotoxin-binding, metabolism- and immune- modulating activities, make natural β-hairpin AMPs an attractive molecular basis for drug design.
Keywords: Antimicrobial peptides